Controllable synthesis of spherical precursor Ni0.8Co0.1Mn0.1(OH)2 for nickel-rich cathode material in Li-ion batteries. Issue 7 (May 2020) - Ding, Yin; Mu, Daobin; Wu, Borong; Zhao, Zhikun; Wang, Rui
Abstract: Synthesis of precursor Ni0.8 Co0.1 Mn0.1 (OH)2 in regular sphere shape as nickel-rich cathode material for Li-ion batteries remains challenging. Here, we report that the morphology of Ni0.8 Co0.1 Mn0.1 (OH)2 can be tuned by controlling the reaction conditions of co-precipitation. The effects of the concentration of NH3 ·H2 O, pH of reaction solution, and stirring speed were studied in detailed. Precursor Ni0.8 Co0.1 Mn0.1 (OH)2 with outstanding spherical hierarchical structure was successfully prepared. The cathode material of LiNi0.8 Co0.1 Mn0.1 O2 was then synthesized based on the prepared Ni0.8 Co0.1 Mn0.1 (OH)2 . It showed excellent crystal structure, morphology and electrochemical properties. Within the voltage range of 2.7–4.3V, the initial discharge specific capacity was 203.7mAh·g -1 and 198.8mAh·g -1 at rate of 0.1C and 0.2C (1C = 200 mA g -1, at 30°C), and the capacity retention were 94.4% and 88.0% for 100cycles and 200cycles (0.2C, at 30°C), respectively.